Alternative treatments to treat perforated peptic ulcer: a systematic review and network meta-analysis of randomized controlled trials - Paschalis Gavriilidis; Carlo Alberto Schena; Salomone Di Saverio; Larry Hromalik; Mehmet Eryilmaz; Fausto Catena; Nicola de’Angelis (World Journal of Emergency Surgery)
Abstract Introduction Perforated peptic ulcers (PPU) represent a critical surgical emergency. Despite the historical predominance of open surgical repair, laparoscopic and endoscopic approaches have shown promise in reducing morbidity and hospital stay. This study aimed to conduct a network meta-analysis comparing open, laparoscopic, and endoscopic interventions for PPU repair. Methods A systematic search of Medline (PubMed), Embase, Cochrane Library, Google Scholar, and the National Institute for Health and Clinical Excellence (NICE) databases identified randomized controlled trials (RCTs) comparing these approaches. The primary outcomes were 30-day mortality and morbidity. Results Eight RCTs including 657 patients were analyzed. Endoscopic interventions were associated with fewer respiratory complications and shorter hospital stays, while the laparoscopic approach demonstrated fewer surgical site infections and less postoperative pain compared to open repair. Other outcomes demonstrated non-significant differences across interventions. Conclusions Prompt resuscitation and surgical repair, either laparoscopic or open, remains the gold standard for PPU. Endoscopic techniques are viable alternatives for small perforations and in selected cases where general anesthesia is contraindicated.